Optical Nanofiber Integrated into Optical Tweezers for In Situ Fiber Probing and Optical Binding Studies - Ivan Gusachenko (Photonics, 2015)
Precise control of particle positioning is desirable in many optical propulsion and sorting applications. Here, we develop an integrated platform for particle manipulation consisting of a combined optical nanofiber and optical tweezers system. We show that consistent and reversible transmission modulations arise when individual silica microspheres are introduced to the nanofiber surface using the optical tweezers. The observed transmission changes depend on both particle and fiber diameter and can be used as a reference point for in situ nanofiber or particle size measurement. Thence, we combine scanning electron microscope (SEM) size measurements with nanofiber transmission data to provide calibration for particle-based fiber assessment. This integrated optical platform provides a method for selective evanescent field manipulation of micron-sized particles and facilitates studies of optical binding and light-particle interaction dynamics.